2020
DOI: 10.1088/2515-7647/ab6a73
|View full text |Cite
|
Sign up to set email alerts
|

Distributed and discrete hydrogen monitoring through optical fiber sensors based on optical frequency domain reflectometry

Abstract: The potential of discrete and distributed fiber-based sensors exploiting the Rayleigh scattering signature of doped amorphous silica is investigated for the real time monitoring of molecular hydrogen (H 2 ) detection. We showed that the impact of the refractive index changes induced by the H 2 diffusion into the silica host matrix can be used to detect and quantify this gas presence through two approaches: first via the related fiber length variation and second through the observed spectral shift. Comparing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Left ventricular assist devices (LVAD) and mild traumatic brain injury are terms in Quadrant II. These terms refer to key areas of research where fiber optic sensing and machine learning have been used to solve critical healthcare problems [31,96,97]. For example, fiber-sensing technology has been used to improve LVAD monitoring and control.…”
Section: Analysis Of Emerging Wordsmentioning
confidence: 99%
See 1 more Smart Citation
“…Left ventricular assist devices (LVAD) and mild traumatic brain injury are terms in Quadrant II. These terms refer to key areas of research where fiber optic sensing and machine learning have been used to solve critical healthcare problems [31,96,97]. For example, fiber-sensing technology has been used to improve LVAD monitoring and control.…”
Section: Analysis Of Emerging Wordsmentioning
confidence: 99%
“…The most commonly measured quantities are deformation (distributed deformation sensing-DSS), temperature (DTS), and acoustics/vibrations (DAS/DVS) [6]. However, DFOS can also directly or indirectly measure other types of quantities, such as displacement [21,22], pressure, force, relative humidity [23][24][25][26][27], radiation [28][29][30], gas concentration [31,32], and more.…”
Section: Introductionmentioning
confidence: 99%
“…For all these environments, the acquisition units can be stored in radiation-free zones, and the sole sensing fiber is exposed to harsh radiation constraints. Several papers have demonstrated that the fiber Rayleigh signature used by OFDR sensing technology is robust against radiation [305]. However, radiation affects the acrylate coating properties, and, by stabilizing the coating through pre-thermal treatments, the precision of the OFDR measurements is increased [221].…”
Section: Distributed Sensorsmentioning
confidence: 99%
“…This has already made DFOSs attractive for a wide range of applications, including structural health monitoring of civil and geotechnical structures [1][2][3][4][5], pipeline and borehole monitoring for leak detection [6], seismic activity monitoring [7][8][9][10] or even the condition monitoring of high-voltage submarine cables [11] and deep earth dynamics in oceans [12]. Even though the most common measurands are temperature and strain, DFOSs can directly or indirectly measure the humidity [13][14][15], pressure [16], displacement [4,17], radiation [18][19][20], gas concentration [21,22], etc.…”
Section: Introductionmentioning
confidence: 99%